2016
DOI: 10.1016/j.leukres.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

The miR-17∼92 cluster contributes to MLL leukemia through the repression of MEIS1 competitor PKNOX1

Abstract: Mixed lineage leukemias have a relatively poor prognosis and arise as a result of translocations between the MLL (KMT2A) gene and one of multiple partner genes. Downstream targets of MLL are aberrantly upregulated and include the developmentally important HOX genes and MEIS1, as well as multiple microRNAs (miRNAs), including the miR-17~92 cluster. Here we examined the contribution of specific miRNAs to MLL leukemias through knockdown studies utilizing custom anti-microRNA oligonucleotides. Combinatorial treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…As shown in Figure A,B; the 3′‐UTR of the Pknox1 mRNA sequence contains two highly conserved target sites of miR‐17 seed family and one conserved target site of miR‐19 seed family. And it has been validated that Pknox1 as a target of both miR‐17 and miR‐19a in a previous study on mixed lineage leukemia . However, the hepatic miR‐19 level was slightly altered in the rat model of T2DM/NAFLD (Figure C).…”
Section: Discussionsupporting
confidence: 57%
“…As shown in Figure A,B; the 3′‐UTR of the Pknox1 mRNA sequence contains two highly conserved target sites of miR‐17 seed family and one conserved target site of miR‐19 seed family. And it has been validated that Pknox1 as a target of both miR‐17 and miR‐19a in a previous study on mixed lineage leukemia . However, the hepatic miR‐19 level was slightly altered in the rat model of T2DM/NAFLD (Figure C).…”
Section: Discussionsupporting
confidence: 57%
“…A study on AML cell lines showed that the miR-19a-3p/HIF-1α axis can be targeted by simvastatin, resulting in the regulation of cell invasion, migration, proliferation and apoptosis [ 33 ]. In mixed-lineage leukemia (MLL) cell lines, anti-miR-19a dramatically reduced the colony-forming abilities of MLL cells compared to controls [ 34 ]. Further research and studies into the cellular mechanisms regulated by miR-181a-5p and miR-19a-3p are required in order to elucidate their role in leukemias and their value as potential targets.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our results, previous study found no significant association between miR-17 and NPM1 or FLT3 mutation status in AML patients [ 30 ]. In addition, there was evidence showing that miR-17 ~ 92 cluster contributed to the MEIS1/HOXA9-mediated transformation of MLL leukemia [ 31 ]. MLL is involved in over 100 different recurrent rearrangements, of which greater than 70 translocation partner genes (TPGs) have now been identified [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%